2012
DOI: 10.4161/biom.20709
|View full text |Cite
|
Sign up to set email alerts
|

Effect of cement fill ratio in loosening of hip implants

Abstract: Femoral loosening is one of the most prevalent causes of revision orthopedic surgeries. Cement mantle thickness has been directly correlated with femoral loosening. If the mantle is too thick, there is an increased risk of radiolucent lines and inconsistent densities. Also, the more bone that is reamed out during the procedure can lead to instability, especially if the quality of the bone is compromised due to osteoporosis. Too thin of a mantle can lead to a higher probability for cement fracture, loosening th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 11 publications
0
12
0
Order By: Relevance
“…More cracks have also been observed in retrievals, when the cement mantle is thin . In fact, numerical studies have shown that thin mantles generate higher stress in the cement, especially close to the stem‐cement interface …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…More cracks have also been observed in retrievals, when the cement mantle is thin . In fact, numerical studies have shown that thin mantles generate higher stress in the cement, especially close to the stem‐cement interface …”
Section: Discussionmentioning
confidence: 99%
“…The thickness of the cement mantle is often indicated as a critical factor . It has been shown that a mantle thicker than 2–3 mm reduces cement stress and micromotions . Conversely, more cracks are found both ex vivo and in vitro where the cement mantle is thin.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The bone has a diameter of 60.2 mm and the ball has a diameter of 28 mm. The thickness of cement mantle used by Gun et al [15] was adopted for calculating contact parameters in this study.…”
Section: Methodsmentioning
confidence: 99%
“…The above-mentioned conditions are usually observed in patients who have an overly active lifestyle or suffer from osteoporosis and/or overweight. They may also occur if the implant is incorrectly installed or if thickness of the cement mantle is wrongly chosen (Gunn et al, 2012), what results from low skills of a surgeon.…”
Section: Introductionmentioning
confidence: 99%